Multi-agent systems and voting: how similar are voting procedures - Janusz Kacprzyk; José M. Merigó; Hannu Nurmi; Slawomir Zadrozny (Switzerland, 2022)
We consider the problem of the evaluation of similarity of voting procedures which are crucial in voting, social choice and related fields. We extend our approach proposed in our former works and compare the voting procedures against some well established and intuitively appealing criteria, and using the number of criteria satisfied as a point of departure for analysis. We also indicate potential of this approach for extending the setting to a fuzzy setting in which the criteria can be satisfied to a degree, and to include a distance based analysis. A possibility to use elements of computational social choice is also indicated.
IPMU 2020: Information Processing and Management of Uncertainty in Knowledge-Based Systems